Lutein/zeaxanthin intake and visual outcomes in adults with healthy eyes: Qualitative gap analysis - Gowri Raman; Danielle Haslam; Esther Avendano; Elizabeth J. Johnson (Cogent Medicine, 2019)
Purpose: Scientific evidence suggests a role for lutein and zeaxanthin, in visual function. The purpose of this research was to summarize the data related to lutein/zeaxanthin intake and visual outcomes in adults with healthy eyes using evidence mapping methods and to describe the research to date that would be useful in guiding future research priorities, systematic reviews, and meta-analyses. Design: A search of Medline®, Cochrane Central, and CAB databases was performed for studies of all designs published from 1946 to October 2016. Our search strategy included lutein, zeaxanthin, meso-zeaxanthin, xanthophylls and carotenoids as well as visual outcomes to include macular pigment density (MPD). Results: Forty-seven studies published in English language were identified and mapped. Most research was conducted in controlled parallel trials (77%) using lutein/zeaxanthin supplements. Studies evaluated effects of lutein/zeaxanthin supplementation (66%) or lutein/zeaxanthin in combination with other nutrients (17%); or evaluated foods rich in lutein/zeaxanthin (17%). MPD (89%) was the most common outcome measure studied. Additional outcome measures included in 47 studies were visual acuity (23%), contrast sensitivity (17%), glare sensitivity (13%), and photostress recovery (11%). Conclusions: This study using evidence mapping found that studies evaluating lutein/zeaxanthin supplementation or intake and visual outcomes had MPD as the most common outcome. We conclude that there is sufficient research to warrant a future systematic review/meta-analysis evaluating the role of lutein/zeaxanthin and visual outcomes in participants with healthy eyes. Of interest would be a systematic review of the studies that evaluated both MPD and visual function to determine the strength of the relationship between these two outcomes in healthy adults.